HUBUNGAN KETEPATAN ESTIMASI DURASI OPERASI DENGAN UTILISASI KAMAR OPERASI ELEKTIF DI INSTALASI BEDAH SENTRAL RSUD Dr. SAIFUL ANWARMALANG (PROFESSIONAL HEALTH JOURNAL, 2024)
The operating room is a vital service in hospitals. The quality of service from theoperating room can be assessed from one indicator, namely operating room utilization.Utilization is the actual time required to carry out additional operations turnover (operationtransfer time) divided by the available time, where turnover averages over 15 minutes.Estimation of the duration of surgery is an important factor in operating room utilization.The aim of this study was to determine the relationship between the accuracy of estimatingthe duration of surgery and the utilization of elective operating rooms in the Central SurgeryInstallation at RSUD Dr. Saiful Anwar Malang. This research method is a prospective cohortfor 19 working days. The sampling technique uses total sampling. The results of the studywere that almost all 284 operations (93.4%) were accurate in estimating the duration of theoperation according to estimates, and the majority of 197 operating rooms (64.8%) hadoperating room utilization in the poor category. Data analysis uses Chi-Square which showsthat the p-value is 0.007 <0.05, which means there is a relationship between the estimatedduration of surgery and operating room utilization. Operating room utilization can beoptimal if one of the factors can be met, namely the operation can be completed on time (onTime) which means the estimation of the duration of the operation must also be correct.Therefore, there is a need for synergy between multidisciplines in the operating room andmanagement in setting schedules and standards for estimating the duration of operations andit is necessary to re-socialize the quality of the operating room for users of the operatingroom and the rooms involved in it, because part of the quality of the operating room is afactors that can influence operating room utilization.